Community Structure of Protease-Producing Bacteria Cultivated From Aquaculture Systems: Potential Impact of a Tropical Environment - Wei, Yali; Bu, Jun; Long, Hao; Zhang, Xiang; Cai, Xiaoni; Huang, Aiyou; Ren, Wei; Xie, Zhenyu (Frontiers in Microbiology, 2021)
Protease-producing bacteria play vital roles in degrading organic matter of aquaculture system, while the knowledge of diversity and bacterial community structure of protease-producing bacteria is limited in this system, especially in tropical region. Herein, 1,179 cultivable protease-producing bacterial strains belonged to Actinobacteria, Firmicutes and Proteobacteria were isolated from tropical aquaculture systems, of which the most abundant genus was Bacillus, followed by Vibrio. The diversity and relative abundance of protease-producing bacteria in sediment were generally higher than those in water. 21 genera from sediment and 16 genera from water were identified, of which Bacillus dominated by B. hwajinpoensis in both and Vibrio dominated by V. owensii in water were the dominant genera. The unique genera in sediment or water accounted for tiny percentage may play important roles in the stability of community structure. 80 V. owensii isolates were clustered into four clusters (ET1-ET4) at 58% of similarity by ERIC-PCR, which was identified as a novel branch of V. owensii. Additionally, V. owensii strains belonged to ET-3 and ET-4 were detected in most aquaculture ponds without outbreak of epidemics, indicating that these protease-producing bacteria may be used as potential beneficial bacteria for wastewater purification. Environmental variables played important roles in shaping protease-producing bacterial diversity and community structure in aquaculture systems. In sediment, DO, COD and salinity as the main factors positively affected the distributions of dominant genus (Vibrio) and unique genera (Planococcus and Psychrobacter), while temperature negatively affected that of Bacillus (except B. hwajinpoensis). In water, Alteromonas as unique genus and Photobacterium were negatively affected by NO3--N and NO2--N, respectively, while pH as the main factor positively affected the distribution of Photobacterium. These findings will lay a foundation for the development of protease-producing bacterial agents for wastewater purification and the construction of an environment-friendly tropical aquaculture model.